"Public procurement challenges and reforms for infrastructure development in South Africa" - Caswell, Grant Sinclair (Department of Public Law, 2021)
The public procurement process in South Africa is governed by a robust regime of laws which includes the Public Finance Management Act1 (PFMA), the Preferential Public Procurement Framework Act2 (PPPFA), the related treasury regulations and a host of internal policies formulated by the various government departments and certain organs of state to deal with aspects of the procurement process which may be unique to those particular departments or organs. In addition to this, the South African courts have also emerged as key role players in the field of South African public procurement law, as they regularly interpret and rule on contentious legal issues which emerge during the procurement process - a natural consequence of the fact that the role and operation of the procurement law regime continue to evolve as government makes use of public procurement to develop infrastructure in South Africa. The courts' involvement in the development of procurement and administrative law in so far as it relates to procurement is particularly evident where the procurement process relates to large-scale infrastructure projects in fields such as transport and energy. Procurement for the purposes of the development of large infrastructure tends to involve a multitude of administrative processes and decisions which are interrelated and which increasingly demand complex and nuanced responsibilities and considerations for government decision-makers to take into account. As a result of this increasingly intricate matrix of responsibilities and considerations, it is very often the case that the procurement of large infrastructure takes place over extended periods of time and, notwithstanding the robust regime of laws which govern public procurement, the South African public procurement system remains plagued by problems such as unnecessary tenders, over billing, false-billing, poor demand management, scope-creep, unjustifiable escalating costs and the unfortunately ever-present element of corruption. The direct result of these mounting problems is that the South African government is presently faced with a substantial amount of legal challenges to its procurement processes - these challenges are launched by a host of interested parties which range from unsuccessful bidders to, amongst others, civil society organisations and the communities affected by the procurement of the infrastructure. In addition, the intricate nature of the procurement process for large infrastructure and the time it takes to conclude the process mean that almost inevitably the legal challenges are launched before the full gamut of administrative decisions have been made and the tender finally awarded. The effects of these challenges are manifest: they create a tension between the need for government to efficiently provide much needed infrastructure in South Africa on the one hand and, on the other, the need for unlawful, unreasonable or procedurally unfair public procurement processes to be legally reviewed. This tension forms the nub of this paper - it will provide a critical analysis of the legal facets of and challenges faced by the South African government's public procurement and administrative law processes in relation to the procurement of large infrastructure and analyse some of the potential reforms to address the challenges.